Strengthening local identity by writing chronicles in the EFL classroom - Flórez González, Alba Milena (Colombian Applied Linguistics Journal, 2018)
This action research study sought to incorporate students’ local identity as the set of traditions, language, history and norms of conduct as a potential element to enhance the foreign language learning process. The purpose of this study was to strengthen local cultural identity in high school students, facilitating a meaningful foreign language learning process and promoting the active participation of students in their local communities (Sharkey, Clavijo, & Ramirez, 2016), through inter-generational dialogue. The research questions proposed were: a) what were the perceptions students had about their local identity? and b) how did high school students strengthen their identity by writing chronicles in English class about their family history? Findings posit the impact of the study on students’ perception about their local identity, how they proudly identify themselves as Villanuevas (people from Villanueva), their active involvement in the community by fostering an intergenerational communication, the improvement on the students’ L2 competence as well as the impact of the sutdy on the researcher teaching process and its cross curricular influence.